Features of medical support of physical training and mass sports events in the Armed Forces of the Russian Federation - V. V. Maslyakov; A. V. Savchenko; A. L. Zhilyaeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Introduction. Physical training is the most important element of the combat readiness of the troops, its goals and objectives are defined by the Manual on Physical Training in the Armed Forces of the Russian Federation. The solution of these tasks should contribute to the formation of military personnel's readiness to endure extreme physical and mental stress during the preparation and conduct of combat operations. Comprehensive provision of physical training in the troops requires the hard work of various services, including the medical service.The purpose of the study. Identify problematic issues of medical support for physical training and sports events in the Armed Forces of the Russian Federation and identify ways to solve them.Materials and methods. The article uses the materials of the work of medical and nursing teams in the medical provision of physical training of units of the Southern Military District from 2016 to 2019. Additionally, the data of an in-depth medical examination of the personnel of some units of the district subordination for 2018 were used.Results and discussion. When analyzing the work of visiting medical and nursing teams during the medical support of passing the standards for physical training, a number of problematic issues were identified. First, there are always military personnel who regularly do not engage in physical training and during the delivery of standards make excessive efforts and work at the limit of their capabilities. Secondly, some exercises are very dangerous, either in terms of injuries or the likelihood of developing complications from the cardiovascular system. All this applies to the medical support of the competition. As an example, the championship of the Armed Forces of the Russian Federation in fire and rescue sports, held from 3 to 6 September 2019 in Rostov-on-Don on the territory of the garrison fire brigade, is given. The program of the competition included passing the obstacle course, climbing the training tower, extinguishing the fire, etc., all very traumatic. Therefore, for the medical support of these competitions, a medical and nursing team of the resuscitation profile was allocated on a reanimobile with specialized stowage, respiratory and oxygen equipment.Conclusion. It is necessary to strictly monitor the correctness of the definition of the group of physical training and the gradual increase in physical activity in order to avoid complications and further progression of diseases or even deaths in military personnel. It is impossible to approach formally the conduct of an in-depth medical examination of military personnel.